Zika virus in transfusion medicine - Diefenbach, Cristiane Fração; de Lima, Valtieri Bortoluzzi; Poleze, Thatyana Cassol; Bier, Bruno Martinazzo; Martins, Juliana Saibt; Krause, Luciana Maria Fontanari (Disciplinarum Scientia | Saúde, 2019)
The Zika virus (ZIKV), belonging to the Flaviviridae family, was first discovered in Africa in 1947. It is responsible for the nation-wide rise in arbovirus-related infections in Brazil. Its main transmission pathway relies on the bite or stinging of humans by virus-infected mosquitoes that belong to the Aedes genera, Aedes aegypti being the most common vector, given its wide distribution throughout tropical and subtropical regions. Transfusion-related transmission pathways have been thoroughly discussed recently due to the large number of asymptomatic patients and the virus’ strong epidemic potential; however, transmission is also possible through sexual and vertical pathways. Overall, clinical outcomes are positive. The most common symptoms experienced by patients are flu-like and similar to dengue (DENV) and chikungunya (CHIKV) virus infections. Primary diagnosis is based on clinical complaints that are typical in infections with this pathogen accompanied by specific molecular tests, more specifically, real-time reverse transcription polymerase chain reaction (RT-PCR). In a few cases, however, there are reports of severe consequences, including Guillain-Barré Syndrome (SGB), neurological damage and fetal malformations like microcephaly. There are no vaccines or ZIKV-specific antiviral therapies. Thus, the ZIKV remains a threat to hemotherapy infection prevention and leading disease control entities.